2009
DOI: 10.3201/eid1504.080940
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Tick Density and Pathogen Endemicity, New Hampshire

Abstract: To assess the endemicity of tick-borne pathogens in New Hampshire, we surveyed adult tick vectors. Pathogens were more prevalent in areas of high tick density, suggesting a correlation between tick establishment and pathogen endemicity. Infection rates in ticks correlated with disease frequency in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 9 publications
(7 reference statements)
1
26
1
Order By: Relevance
“…Epidemiological studies often involve isolation and characterization of multiple B. burgdorferi strains from regions of endemicity (58,59,66,67,102). However, there is no simple test to determine whether a new isolate is indeed a very different strain or is similar to one of the strains previously isolated from the same region.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies often involve isolation and characterization of multiple B. burgdorferi strains from regions of endemicity (58,59,66,67,102). However, there is no simple test to determine whether a new isolate is indeed a very different strain or is similar to one of the strains previously isolated from the same region.…”
Section: Discussionmentioning
confidence: 99%
“…Well delineated areas of Connecticut have been identified as locations where B. microti is highly endemic, but distally from these areas of high endemicity, the parasite's distribution decreases and is less well defined (62). Similarly, our current understanding of the parasite's distribution is dynamic, with evidence of human infections now being described in Maine and New Hampshire (83,92,123). This may reflect an actual expansion of the parasite's geographic distribution or increased recognition of infection, perhaps acquired elsewhere, by physicians.…”
Section: Exclusion Factorsmentioning
confidence: 99%
“…It has been reported that a wet January-March may aid tick survival and that there is an association between tick establishment and LB endemicity in ticks. 4,23 Moreover, it has been reported that infection rates in ticks correlate with disease frequency in humans. 23 In the east of Scotland, January-March rainfall peaked in 2008, coinciding with the dramatic rise of LB in Tayside (Figure 2A).…”
Section: Clinical Categorymentioning
confidence: 99%
“…4,23 Moreover, it has been reported that infection rates in ticks correlate with disease frequency in humans. 23 In the east of Scotland, January-March rainfall peaked in 2008, coinciding with the dramatic rise of LB in Tayside (Figure 2A). That year also had a dry summer, potentially leading to increased human exposure.…”
Section: Clinical Categorymentioning
confidence: 99%